SIMULACRUM PEMANFAATAN ARTIFICIAL INTELLIGANCE PADA KAMPANYE POLITIK PILPRES DAN WAPRES 2024 MELALUI VIDEO TIKTOK - Triartanto, A. Yudo; Mutiah, Tuty; Adhi Dharma Suriyanto; Jaka Atmaja; Chepi Nurdiansyah; Fitriyanto (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Digital systems and networks (internet), which have increasingly developed recently, have triggered various technological innovations. One of the innovations that has received great attention from citizens of the world - indications are that there are various technological discoveries through applications on cellphones - is the presence of Artificial Intelligence (AI) technology. In formats in the media realm - whether films, videos, photos, music or text - AI technology has been presented and used with its sophistication. Although the use of AI actually becomes a simulacrum in text messages - borrowing the concept of simulacrum from Jean Baudrillard - in a number of cinema films and social media. Specifically on social media, AI technology is being used by a number of political parties and success teams or spin doctors from each pair of presidential and vicepresidential candidates in 2024 in delivering their political campaigns. The content of political campaign messages published on social media regarding the election of presidential and vicepresidential candidates (presidential and vice presidential candidates) - including Facebook, YouTube, effective in the context of delivering communication messages. The range of communication or political campaign messages that are appropriate and effective - via cell phones or mobile phones and laptops - is able to reach and shape personal perceptions through cognitive, affective and conative structures or behavior towards potential voters. Although, this research only examines political campaigns using the concept of simulacrum theory and political communication (campaigns) on short videos tens of seconds long that utilize AI technology and are distributed on social media regarding the election of presidential and vice presidential candidates, especially TikTok - considering this social media has penetration and is the highest usage choice – regarding the election of presidential and vice presidential candidates for the period 2024 – 2029.